2011
DOI: 10.1007/s11605-011-1585-8
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Etiology and Management of Hyperinsulinemic Hypoglycemia After Roux-en-Y Gastric Bypass

Abstract: Treatment of hypoglycemia after RYGB should begin with strict dietary (low carbohydrate) alteration and may require a trial of diazoxide, octreotide, or calcium-channel antagonists, among other drugs. Surgical therapy should include consideration of a restrictive form of bariatric procedure, with or without reconstitution of gastrointestinal continuity. Partial or total pancreatic resection should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 109 publications
(102 reference statements)
3
43
0
5
Order By: Relevance
“…This finding is supported by the data from a Swedish nationwide cohort study, where incidence of hospitalization for hypoglycemia after RyGB was found to be 0.2% as compared to only 0.04% in the reference population (31). Most cases of hypoglycemia after RyGB are successfully treated with low carbohydrate diet or with diazoxide, octreotide, acarbose or calcium-channel blockers (32). In severe cases, surgical intervention (reversal of RyGB, conversion of RyGB to SG, placement of adjustable gastric band over RyGB, or even subtotal/total pancreatectomy) has been proposed.…”
Section: Surgery Versus Conventional Treatmentsupporting
confidence: 52%
“…This finding is supported by the data from a Swedish nationwide cohort study, where incidence of hospitalization for hypoglycemia after RyGB was found to be 0.2% as compared to only 0.04% in the reference population (31). Most cases of hypoglycemia after RyGB are successfully treated with low carbohydrate diet or with diazoxide, octreotide, acarbose or calcium-channel blockers (32). In severe cases, surgical intervention (reversal of RyGB, conversion of RyGB to SG, placement of adjustable gastric band over RyGB, or even subtotal/total pancreatectomy) has been proposed.…”
Section: Surgery Versus Conventional Treatmentsupporting
confidence: 52%
“…Criteria for assessment of effect of bariatric surgery on optimization of metabolic status and some other co-morbid conditions [58] : -HbA1c ≤ 6%, no hypoglycaemia, total cholesterol < 4 mmol/l, LDL-cholesterol < 2 mmol/l, triglycerides < 2.2 mmol/l, blood pressure < 135/85 mmHg, >15% weight loss, or lowering of HbA1c by >20%, LDL< 2.3 mmol/l, blood pressure < 135/85 mm Hg with reduced medication from pre-operative status. In cases of postprandial hypoglycaemic symptoms, evidence for lowered blood glucose concurrent with symptoms should be looked for; patients should first be advised on dietary changes (low carbohydrate diets, regular meal times); second-line drug treatment may be considered, such as acarbose, calcium-channel antagonists, diazoxide, octreotide (EL C [188][189][190][191][192] .) Special care must be taken for: -The possible nutritional deficiencies such as vitamin, protein and other micronutrients.…”
Section: Follow-upmentioning
confidence: 99%
“…This alteration in anatomy gives rise to side effects: early dumping symptoms and in some cases later discomfort due to postprandial hypoglycemia (PPHG) (2). The dumping syndrome is characterized as an attack within 10-30 min after eating with symptoms of dizziness, diaphoresis, flushing, nausea, bloating, and fatigue.…”
Section: Introductionmentioning
confidence: 99%